Protecting the right to pursue a livelihood for foreign-trained professionals: toward building an enabling regulatory system. (2016) - Houle, France
The literature developed in Canada on the impact of conditions imposed by professional associations on the fundamental rights of foreign-trained professionals has focused primarily on the right to equality, while the discussion could also be centred on the right to pursue a livelihood. This article suggests a post-welfare state interpretation of the right to pursue a livelihood based on the capabilities approach and the enabling state. For foreign-trained professionals immigrating to a new country, empowerment starts with the ability to earn a living in their profession as quickly as possible. To achieve this goal, the author suggests that regulatory systems pertaining to the recognition of qualifications of foreign-trained professionals should be proportionate, contain as few restrictions as possible and take the professional experience of applications into account.